2015
DOI: 10.1007/s10552-015-0699-9
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease severity and cancer risk in postmenopausal women: the Buffalo OsteoPerio Study

Abstract: Purpose Few prospective studies have reported on relationships between objective periodontal disease (PD) measures and cancer risk. This association was examined in 1,337 postmenopausal women participating in the Buffalo OsteoPerio Study. Methods Oral alveolar crestal bone height (ACH) was measured using oral radiographs. Incident cancers were adjudicated with medical records. Hazard ratios (HR) and 95% confidence intervals (CI) for associations between ACH and incident cancer outcomes were estimated using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 35 publications
4
86
0
Order By: Relevance
“…However, analyses of specific hematological cancers, including distinct NHL subtypes, were not possible given that only 24 cases were identified (including 11 exposed cases). 37 No association between periodontitis and hematological cancers was observed in a nationwide study in Taiwan. 38 In a Swedish registry-based case-control study, gingivitis and periodontitis was found to be associated with increased risk of lymphoplasmacytic lymphoma/Waldenstr€ om macroglobulinemia (odds ratio: 1.9; 95% CI: 1.3, 2.7), 39 a rarer subtype of NHL.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, analyses of specific hematological cancers, including distinct NHL subtypes, were not possible given that only 24 cases were identified (including 11 exposed cases). 37 No association between periodontitis and hematological cancers was observed in a nationwide study in Taiwan. 38 In a Swedish registry-based case-control study, gingivitis and periodontitis was found to be associated with increased risk of lymphoplasmacytic lymphoma/Waldenstr€ om macroglobulinemia (odds ratio: 1.9; 95% CI: 1.3, 2.7), 39 a rarer subtype of NHL.…”
Section: Discussionmentioning
confidence: 98%
“…However, analyses of specific hematological cancers, including distinct NHL subtypes, were not possible given that only 24 cases were identified (including 11 exposed cases) [37]. No association between periodontitis and hematological cancers was observed in a nationwide study in Taiwan [38].…”
Section: Discussionmentioning
confidence: 99%
“…15 There is ever-increasing evidence, suggesting that PD appears to be associated with lung cancer. [16][17][18][19][20][21] In the absence of effective therapeutic methods, it is necessary to identify modifiable determinants of lung cancer risk. Zeng et al published the first meta-analysis on this topic in 2016, 22 which included five studies published from 2003 to 2014, followed by Michaud et al with another one in the following year, 23 including five studies published from 2011 to 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a great deal of research effort has been dedicated to understanding the impact of the oral microbial burden on systemic health. It is well recognized that periodontal infection increases the level of inflammatory markers in the blood, and several studies [14][15][16][17] have linked this persistent inflammation to the development of different types of cancer, including breast cancer [18,19,25]. Therefore, defining the microbial profile of women with breast cancer and periodontitis is important contributory data to our understanding of the relationship between periodontitis and this systemic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ChP promotes systemic inflammation via translocation of oral bacteria, bacterial toxins, and inflammatory mediators through frequent transient bacteremia that would heighten the systemic burden and could promote cellular differentiation [4,13]. In addition, ChP has also been associated with cancers of the head and neck [14,15], pancreas [16], lung [17], and more recently breast cancer [18,19].…”
Section: Introductionmentioning
confidence: 99%